Gut Mucosal Microbiome Signatures of Colorectal Cancer Differ According to BMI Status - Shaw, Sophie; Berry, Susan; Thomson, John; Murray, Graeme I.; El-Omar, Emad; Hold, Georgina L. (Frontiers in Medicine, 2022)
Background: Carrying excess body weight is a strong risk factor for colorectal cancer (CRC) development with ~11% of CRC cases in Europe linked to being overweight. The mechanisms through which excess body weight influences CRC development are not well understood but studies suggest the presence of chronic low-grade inflammation and changes in the gut microbiota are involved. Aim: To compare the mucosal associated microbiota of CRC patients to see whether carrying excess body weight was associated with a unique CRC microbial signature. Methods: Microbiota signatures from colonic mucosal biopsies from CRC lesions and adjacent normal mucosal samples from 20 patients with overt CRC were compared with 11 healthy controls to see if having a BMI of >25kg/m2 influenced colonic microbial composition. Results: Colonic mucosa samples from patients with CRC confirmed previously reported over-abundance of Fusobacteria associated with CRC but also an increase in Fusobacteria and Prevotella were associated with a BMI of >25kg/m2. Correlation analysis of bacterial taxa indicated co-exclusive relationships were more common in CRC patients with a a BMI of >25kg/m2 with an increase in transphylum relationships also seen in this patient group. Conclusions: The findings suggest that gut microbiota composition in CRC patients is influenced by BMI status. Further understanding/defining these differences will provide important information in terms of developing novel pre-onset screening and providing post-manifestation therapeutic intervention.